Acting in Solidarity: Cross-Group Contact between Disadvantaged Group Members and Advantaged Group Allies - Droogendyk, Lisa; Wright, Stephen C.; Lubensky, Micah; Louis, Winnifred R. (Journal of social issues, 2016)
The actions of advantaged group activists (sometimes called “allies”) are admirable, and they likely make meaningful contributions to the movements they support. However, a nuanced understanding of the role of advantaged group allies must also consider the potential challenges of their participation. Both in their everyday lives and during their activist work, advantaged group allies are especially likely to have direct contact with disadvantaged group members. This article considers when such contact may harm rather than help resistance movements by disadvantaged groups. We also suggest that to avoid these undermining effects, advantaged group allies must effectively communicate support for social change, understand the implications of their own privilege, offer autonomy‐oriented support, and resist the urge to increase their own feelings of inclusion by co‐opting relevant marginalized social identities.